Creative Industries in Canada - Thompson, Cheryl; Campbell, Miranda (Canadian Scholars, 2022)
Keywords: Cultural industries.; Irina

Laughter from the Sidelines: Precarious Work in the Canadian Comedy Industry - Trusolino, Madison (Creative Industries in Canada, 2022)
Creative Industries in Canada is a foundational text that encourages students to think critically about creative industries within a Canadian context and interrogate the current state and future possibilities of the industry. While much of current creative industries literature concerns the United Kingdom, the United States, and Asia, this text captures the breadth of how Canadian industries are organized and experienced, and how they operate.This ambitious collection aims to guide students through the current landscape of Canadian creative industries through three thematic sections. “Production” collects chapters focused on how national discourses and identities are produced through creative industries and the tensions that exist between policy and media. “Participation” explores how we engage with these industries in different roles: as consumer, creator, policy-maker, and more. “Pedagogies” explores how education impacts inclusion and visibility in creative industries.Truly intersectional, Creative Industries in Canada provides students with practical industry knowledge and frameworks to explore the current state of the field and its future. With a broad application to many undergraduate programs, this text is a must-read resource for those pursuing media studies, arts management, creative and cultural industries studies, communications, and arts and humanities.
Keywords: Bibliographie; Business & Economics / Industries / Media & Communications; Nettoyer; Social Science / Media Studies; Sophie-Anne